Association of body weight gain with subsequent cardiovascular event in non-obese general population without overt cardiovascular disease. (September 2020) - Kaneko, Hidehiro; Itoh, Hidetaka; Yotsumoto, Haruki; Kiriyama, Hiroyuki; Kamon, Tatsuya; Fujiu, Katsuhito; Morita, Kojiro; Michihata, Nobuaki; Jo, Taisuke; Morita, Hiroyuki; Yasunaga, Hideo; Komuro, Issei
Abstract: Background: Body weight (BW) gain in adulthood frequently leads to the development of obesity and is associated with subsequent cardiovascular disease (CVD). However, the pathological significance of BW gain in non-obese individuals is not fully understood. Methods and results: Using data from a nationwide epidemiological database, we studied 1, 558, 774 non-obese subjects aged ≥20 years and without prior history of CVD. The subjects' mean age was 44.7 ± 11.2 years, and 853, 391 subjects (54.7%) were male. BW gain, which was defined as BW gain of ≥10 kg from the age of 20 years, was seen in 302, 997 subjects (19.4%). Subjects with BW gain were older and more likely to be male than those without BW gain. Body mass index and waist circumference were higher in subjects with BW gain. The prevalence of classical CVD risk factors was higher in subjects with BW gain. Kaplan–Meier curves and log-rank tests showed that subjects with BW gain had higher incidences of composite endpoints, including myocardial infarction, angina pectoris, and stroke. Multivariable Cox regression analysis including other covariates presented that BW gain was independently associated with the incidence of composite endpoint (Hazard ratio 1.10, 95% confidence interval 1.07–1.13, p < 0.001). Subgroup analyses showed that the association of BW gain with the development of CVD was observed regardless of age, sex, and body mass index. Conclusion: Subjects with BW gain of ≥10 kg from the age of 20 years had high incidence of cardiovascular events even if they did not yet develop obesity. The results suggest the significance of substantial BW gain in adulthood in the development of subsequent CVDs. Graphical abstract: Image 1